Orzecznictwo sądów amerykańskich w sprawach niewolnictwa – pomiędzy formalizmem a subwersją - Zajadło, Jerzy (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
Article discusses a dilemma of judge facing a possibility (or necessity) of applying judicial disobedience. From the philosophical as well as theoretical point of view, the most intriguing would be an instance of judicial disobedience when applied to a state of democracy and the rule of law. In order to (re-)construct such an instance, the article traces the reader back to the middle of the 19th Century, when the moral conscience of (at least) some of American judges drove them to searching for the sound justification of judicial disobedience when faced with problem of slavery.